Javanese Medaka, Oryzias javanicus, an excellent model fish for microplastic research in Malaysia and Indonesia - Pratiwi, Hilda Mardiana; Rusni, Suhaila; Inoue, Koji (Springer Nature, 2026)
In recent years, microplastics (MPs) have become a significant threat to marine ecosystems in Southeast Asia, especially in Malaysia and Indonesia. It is crucial to conduct field studies to assess MP status, but laboratory studies are also vital to understand the toxicity of MPs on organisms. This work gathered important information for estimating trends, resolving questions, and selecting suitable model fish to develop future MP studies at research institutions in Malaysia and Indonesia. Using the bibliometric analysis approach with the Web of Science database, we investigated recent progress of MP studies and the use of local fish as model animals for toxicity tests in both countries. Analysis of 197 articles published between 2017 and 2023 showed that publications related to MP research have increased exponentially in recent years. These studies predominantly focused on MP detection in the field. Meanwhile, laboratory research that investigated impacts of MPs on animals, especially fish, is still limited. Additionally, we identified the top ten species of fish that are employed for laboratory testing in both countries. Compared to other fishes on the list, Javanese medaka (Oryzias javanicus), a Southeast Asian native medaka, offers numerous benefits, such as smaller size, shorter spawning, easy maintenance, euryhalinity, and availability of genomic information. Therefore, Javanese medaka is a very useful test fish for studying MPs in Malaysia and Indonesia.